THE COMBINATION OF DENOTATIVE AND CONNOTATIVE ELEMENTS OF THE MEANING OF THE WORD OF THE COMPARED LANGUAGE UNITS - Ruziev Khusniddin Bakhritdinovich (Лучшие интеллектуальные исследования, 2024)
Abstract: This article deal with the combination of denotative and connotative elements of the meaning of the word of the compared language units